Parental supportive and intrusive directives during dyadic interactions in relation to concurrent skills of preterm and full-term toddlers at age 2 years - Ataman Devrim, Merve; Quigley, Jean; Nixon, Elizabeth (Springer, Current Psychology, 2024)
This study investigates whether parental supportive (following) and intrusive (redirecting child’s attention) verbal directives are influenced by parent gender and birth status, and whether any associations between parental supportive/intrusive directives and developmental outcomes are moderated by birth status. Seventeen preterm and 31 full-term toddlers took part with both parents. Parental directives were coded using transcriptions of dyadic free-play interactions. Toddlers’ cognitive, language, and social-emotional skills were assessed via the Bayley-III scales and executive function skills were measured via parental report. 2x2 mixed design ANOVAs showed no significant effect of parent gender, birth status, or interaction, on parental directives. Moderation analyses demonstrated significant associations between fathers’, but not mothers’, intrusive directives and toddlers’ cognitive and expressive language scores for preterm, but not full-term, toddlers. Although parents of preterm and full-term toddlers used similar supportive/intrusive directives, fathers of preterm toddlers who exhibited poorer expressive language and cognitive skills used more intrusive directives.
Keywords: preterm, toddlers, directiveness, mothers, fathers, parent-child interaction; CHILD DEVELOPMENT; FAMILY; PARENT-CHILD RELATIONS; Psychology